2022
DOI: 10.1002/da.23287
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity among men using anabolic steroids

Abstract: Objective: The purpose of this study was to investigate the psychiatric morbidity among men with abuse of anabolic steroids. Methods:The design is a retrospectively matched cohort study. Five hundred and fourty-five males, who tested positive for anabolic steroids in Danish fitness centers during the period January 3, 2006 to March 1, 2018, were matched with 5450 randomly chosen male controls. Data was cross-referenced with seven national registers pertaining to information about education, employment status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…In fact, depression, anxiety and fatigue were all side effects more commonly reported among those who sought treatment, and mental health issues was the second most common reason for seeking health services, a finding that is in concordance with previous studies [21,35]. AAS use has recently shown to be associated with increased use of prescribed psychopharmacological treatment including anxiolytics [64], which was also reflected in the present study as treatment seekers reported significantly more current use of prescribed anxiolytics compared to the non-treatment seeking group. Moreover, it is likely that predefined perceptions of which treatment each health service can provide will influence health service engagement [27].…”
Section: Discussionsupporting
confidence: 88%
“…In fact, depression, anxiety and fatigue were all side effects more commonly reported among those who sought treatment, and mental health issues was the second most common reason for seeking health services, a finding that is in concordance with previous studies [21,35]. AAS use has recently shown to be associated with increased use of prescribed psychopharmacological treatment including anxiolytics [64], which was also reflected in the present study as treatment seekers reported significantly more current use of prescribed anxiolytics compared to the non-treatment seeking group. Moreover, it is likely that predefined perceptions of which treatment each health service can provide will influence health service engagement [27].…”
Section: Discussionsupporting
confidence: 88%
“…Narcissism has previously been linked to appearance‐ and fitness‐enhancing behaviors in general (Martinovic et al., 2022 ; Miller & Mesagno, 2014 ). The finding of no psychopathology in a group of the AAS users in our sample is expected, as it resembles several other studies finding that the majority of AAS users reported minimal psychiatric effects, or finding few significant psychopathological differences between weightlifting controls and AAS users as a whole (Bahrke et al., 1996 ; Moss et al., 1992 ; Tricker et al., 1996 ; Windfeld‐Mathiasen et al., 2022 ). The differences that we observed in psychiatric morbidity both between AAS users and weightlifting controls, and within the group of AAS users, may be affected by many different factors linked to AAS use.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, thinner cortex in various regions and less total grey matter, cerebral cortex and putamen are also linked to the long-term usage of ASS (Bjørnebekk et al, 2017). With all this knowledge, we can conclude that ASS abusing causing variety of mental health problems and new studies are on the way to shed light on the neuro-physiatric consequences as well (Windfeld-Mathiasen et al, 2022).…”
Section: Anabolic Androgenic Steroid Dependencementioning
confidence: 92%